ARREST AFTER CONVICTION IN THE 2nd INSTANCE: ARGUMENTS IN THE BRAZILIAN LEGISLATION AND CHANGES IN THE UNDERSTANDING OF THE STF - Carrero Teixeira, Felippe (Revista Gênero e Interdisciplinaridade, 2023)
The present work aims to discuss prison after conviction in second instance, addressing constitutional aspects, the panorama of Brazilian precedents and the current understanding of the Federal Supreme Court. Using bibliographical research, regarding doctrine, jurisprudence and legislation, attention is given to the theme from the perspective of the principle of the presumption of innocence. Therefore, an analysis is made of the constitutional principle of the presumption of innocence, of existing prisons in the Brazilian legal system and, then, the doctrinal understanding is debated to, finally, reach the jurisprudential modifications within the scope of the Federal Supreme Court.